End-to-end encrypted messaging - Oppliger, Rolf (Artech House information security and privacy series., 2020)
This book introduces the core technologies that are used for Internet messaging. The major cryptographic techniques that are used for secure and end to end encryption (E2EE) messaging on the Internet are explored. The notion of "secure" and E2EE messaging and various approaches to address it is discussed. A comprehensive treatment of Pretty Good Privacy (PGP) and OpenPGP as well as Secure/Multipurpose Internet Mail Extensions (S/MIME) is given, as well as the evolutionary improvements to PGP/OpenPGP and S/MIME that have been proposed in the past. The different E2EE messengers that have been made available in the last decade are provided and what Signal protocol that is core to E2EE messaging today.The book explains how the Signal protocol is implemented in WhatsApp, and addresses privacy issues related to E2EE messengers. It addresses the notion of self-destructing messages (as originally introduced by SnapChat) and the use of metadata to perform traffic analysis.